Pathological significance of Epidermal Growth Factor Receptor (EGFR), Vascular Endothelial Growth Factor (VEGF), Chemokine Receptor 4 (CXCR4) and Vimentin expression by colon carcinoma cells - De Zoysa, M.I.M.; Samarasekera, D.N.; Senarath, L.D.J.U.; Samarasekera, C.A.; Reid, C.B.; Lokuhetty, M.D.S. (My University, 2012)
Colon carcinoma has a worldwide incidence of over one million with a 5 year survival rate of <20% for metastatic disease. Identification of metastasis related biomarkers will enable risk evaluation of metastasis in colon carcinoma.